Prevalence of negative symptoms in outpatients with schizophrenia spectrum disorders treated with antipsychotics in routine clinical practice: findings from the CLAMORS study - Bobes, Julio; Arango, Celso; Garcia-Garcia, Margarida; Rejas, Javier (The journal of clinical psychiatry, 2010)
To analyze the prevalence of negative symptoms in antipsychotic-treated outpatients with schizophrenia spectrum disorders. A cross-sectional, retrospective multicenter study was carried out between May 2004 and April 2005 in 1,704 adult psychiatric outpatients meeting DSM-IV criteria for schizophrenia, schizophreniform, or schizoaffective disorder. We used 5 items of the Positive and Negative Syndrome Scale (PANSS) negative symptoms subscale to individually determine the presence of a negative symptom when the score on the item was > 3. Primary negative symptoms were considered present when patients fulfilled all of the following: > 3 score on the corresponding item; < 3 score on any positive item; no extrapyramidal symptoms; <or= 3 score on anxiety and depression items; dose of haloperidol, when applicable, <or= 15 mg/d; and no antiparkinsonian treatment. A total of 1,452 evaluable patients (863 men, 60.9%), 40.7 +/- 12.2 (mean +/- SD) years of age, were included. One or more negative symptoms were present in 57.6% of patients, with primary negative symptoms in 12.9% of subjects. The most frequent negative symptom items were social withdrawal (45.8%), emotional withdrawal (39.1%), poor rapport (35.8%), and blunted affect (33.1%). Negative symptoms (1-blunted affect, 2-emotional withdrawal, 3-poor rapport, 4-social withdrawal, 5-verbal fluency) were most associated with maleness (symptom 4); age > 40/45 years (men/women; symptoms 1,2,4); single/unmarried status (symptoms 2-4); unemployment (symptoms 3,4); higher score on the Clinical Global Impressions (CGI) scale and PANSS total score (symptoms 1-5); lower score on the PANSS positive symptoms subscale (symptoms 1,3); more than 52 weeks of treatment (symptoms 1-3,5); and high antipsychotic dose (symptom 2). The prevalence of negative symptoms in patients with schizophrenia spectrum disorders treated with antipsychotics in routine clinical practice not only is still considerably high but also seems to be related to poorer functioning, unemployment, greater severity, and less positive symptomatology and higher antipsychotic dose.